احادیث طیبہ کے متعلق مستشرقین کے اعتراضات کا علمی و تنقیدی جائزہ: A Scholarly and Critical Review of the Objections of Orientalists Regarding Hadith Tayyaba - Muhammad Riaz ud din,; Muhammad Fiaz Ud Din,; Shabnam Begum, (Al Manhal Research Journal, 2024)
Islamic Studies Qur'an and Hadith Sharia Law By the end of the 20th century, the study of hadith had developed considerably and received increasing attention in both the Muslim and Western worlds. The role of hadith has attracted the attention of Orientalists who have sought to identify the origins of Islam and its legal and religious institutions. Therefore, the Orientalists made every possible effort to distance the Muslims from the Qur'an and Hadith. And under his conspiracies, he raised objections to the Quran and Hadith in order to cast doubt on the Muslims. This article is an analytical review of the objections raised by the Orientalists on the Hadith-e-Taiba, a research-based article in which the various contradictions of the Western Muhadditheen in relation to the criticism of the chain of Hadith/Sinaad are described.